2014
DOI: 10.1111/cen.12565
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog mutations are not a common cause of congenital hypopituitarism in the absence of complex midline cerebral defects

Abstract: SHH mutations or copy number variations are not a common cause of congenital hypopituitarism in patients without complex midline cerebral defects. GLI2 variants are found in some patients with congenital hypopituitarism without complex midline cerebral defects or septo-optic dysplasia. However, functional analyses of these variants are needed to strengthen genotype-phenotype relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The exact frequency ofGLI2 mutations in patients with hypopituitarism is difficult to establish due to the large phenotypic variability of the studied cohorts. [17][18][19]21,24 Moreover, GLI2 is a large and highly In the present study, we report five unrelated subjects bearing five non-synonymous GLI2 variations in a cohort of 145 CPHD patients with or without extra-pituitary findings all at the heterozygous state. All the variants were absent in the public databases or if present, the frequency was not reported or extremely low (0.0001735) and predicted to be pathogenic by at least one prediction software ( The most striking results were observed for theGLI2ΔN-p.575H…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The exact frequency ofGLI2 mutations in patients with hypopituitarism is difficult to establish due to the large phenotypic variability of the studied cohorts. [17][18][19]21,24 Moreover, GLI2 is a large and highly In the present study, we report five unrelated subjects bearing five non-synonymous GLI2 variations in a cohort of 145 CPHD patients with or without extra-pituitary findings all at the heterozygous state. All the variants were absent in the public databases or if present, the frequency was not reported or extremely low (0.0001735) and predicted to be pathogenic by at least one prediction software ( The most striking results were observed for theGLI2ΔN-p.575H…”
Section: Discussionmentioning
confidence: 82%
“…The exact frequency of GLI2 mutations in patients with hypopituitarism is difficult to establish due to the large phenotypic variability of the studied cohorts . Moreover, GLI2 is a large and highly polymorphic gene with several rare variations reported in public databases making the establishment of the variants pathogenicity difficult without performing functional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the six patients with hypopituitarism, four had IGHD and two had CPHD, independent of age. The two patients reported by Paulo et al (2015). had a median solitary maxillary incisor, one with cleft palate, but this was not observed in the patients studied by França et al (2010).…”
Section: Human Mutationsmentioning
confidence: 87%
“…The largest family with GLI2 mutations reported to date had the p.Leu788fsX794 mutation (França et al 2010, Paulo et al 2015. In the family reported by França et al (2010), the ten subjects who tested positive for the mutation also had polydactyly, whereas in the two distant relatives with the same mutation studied by Paulo et al (2015) in a different city, polydactyly was not observed. Among the six patients with hypopituitarism, four had IGHD and two had CPHD, independent of age.…”
Section: Human Mutationsmentioning
confidence: 96%
See 1 more Smart Citation